Evaluation of software to construct genetic linkage maps in plants - Santos, Jenifer Camila Godoy dos (2019)
Genetic maps are useful tools in breeding programs and evolutionary studies. Since the publication of the first map, several concepts have been proposed and implemented in various mapping software. Each software presents different characteristics for the construction of maps. For example, aspects such as availability of source code, licenses, tutorials, and operating system need to be considered. There are also important points related to the statistical methods employed. In this context, the users\' choice can often be a complicated task. The objectives here were: i) to present the main software with free licenses developed in recent years; ii) construct linkage maps using these software and, iii) evaluate them from the point of view of users. The software considered were: OneMap, Lep-MAP, HighMap, Lep-MAP2, Flipper, Lep-MAP3, ASMap, and GUSMap. This work can guide researchers about the free tools available to construct genetic maps.